Application of Trichoderma Biofertilizer on Sweet Potato Plants (Ipomoea Batatas L.) - Izzat Khadafi Haikal; S Sutarman (CV. Media Digital Publikasi Indonesia, 2025)
The objective of this study was to determine the effect of Trichoderma esperellum biological agent applied through soil treatment and foliar spray, as well as the possibility of their interaction on the vegetative growth of sweet potato plants. The density of fungal spores in the propagule suspension ready to be sprayed onto the canopy surface was the same as that contained in the solid form for fertilization application, namely 105 CFU.mL-1. The experiment was arranged factorially in a Randomized Block Design (RBD) with four replicates. The variables observed were plant height, number of leaves, stem diameter, and harvest weight per 1.5 m2 plot area. The data were analyzed using Analysis of Variance followed by a 5% BNJ test. The results showed that the application of Trichoderma biofertilizer as soil fertilization had a significant effect on plant growth and harvest weight, while application through canopy spraying had no significant effect. The interaction effect was only significant for plant height. Fertilizer application at planting time yielded the highest results at the end of the observation period, namely 34.0 cm, 114 shoots, 10.05 cm, and 2,686.6 g for plant height, number of leaves, stem diameter, and harvest weight, respectively.